2012
DOI: 10.1371/journal.pone.0051739
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of GSTA1 Expression Are Required for Caco-2 Cell Proliferation

Abstract: The colonic epithelium continuously regenerates with transitions through various cellular phases including proliferation, differentiation and cell death via apoptosis. Human colonic adenocarcinoma (Caco-2) cells in culture undergo spontaneous differentiation into mature enterocytes in association with progressive increases in expression of glutathione S-transferase alpha-1 (GSTA1). We hypothesize that GSTA1 plays a functional role in controlling proliferation, differentiation and apoptosis in Caco-2 cells. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…Previous studies have demonstrated that GSTA1 overexpression protects tumor cells from doxorubicin and reactive oxygen species-induced apoptosis (31)(32)(33)(34). GSTA1 also serves a role in regulating the proliferation of Caco-2 cells (35). Recently, it has been demonstrated that GSTA1 promotes the proliferation of lung cancer cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that GSTA1 overexpression protects tumor cells from doxorubicin and reactive oxygen species-induced apoptosis (31)(32)(33)(34). GSTA1 also serves a role in regulating the proliferation of Caco-2 cells (35). Recently, it has been demonstrated that GSTA1 promotes the proliferation of lung cancer cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…Eight isoforms of cytosolic-soluble GSTs have been recognized in humans, including α, Îș, ÎŒ, π, σ, Ξ, ζ, and ω 3,4 . Glutathione S-transferase α1 (GSTA1, Gene ID: 2938) has shown both stimulatory [5][6][7][8] and inhibitory effects [9][10][11][12] on tumorigenesis. The association between genetic polymorphism of GSTA1 and susceptibility to cancer has been discussed in previous studies [13][14][15] , but…”
Section: Introductionmentioning
confidence: 99%
“…ALP1 and VIL1 are established markers for enterocyte differentiation and have been used previously to assess Caco-2 differentiation. 17,35,36 Their expression was significantly higher already before differentiation in the modified sublines than in wild-type Caco-2 cells, and increased 1.5-to 4-fold in all cell types during differentiation in culture. The enhanced expression of ALP1 and VIL1 suggests that introduction of chimeric NRs can stimulate Caco-2 differentiation toward an enterocytic phenotype.…”
Section: Cell Differentiation and Permeation Propertiesmentioning
confidence: 92%